Relación entre el gasto público en turismo del Gobierno Regional de Loreto y el arribo de turistas en Loreto 2015-2023 - Chota Macuyama, Lizeth (2025)
The arrival of tourists represents the arrival of visitors to the region for tourism purposes, which is important for economic development, generating greater income from tourism activity, also, public spending on tourism is presented as a tool that could boost the development of tourism in specific sectors. In this sense, the research raises the main objective of determining the relationship between the spending of the Regional Government of Loreto on tourism and the arrival of tourists in the department of Loreto period 2015-2023. Likewise, the research is developed through the type, quantitative, correlational level and non-experimental design of longitudinal data, including as a study population 36 quarterly data on the execution of tourism spending by the Regional Government of Loreto and the arrival of tourists in Loreto, in the period 2015 2023. It was observed that public spending on tourism presented a very stable behavior for an adequate inferential analysis until 2019, so it was decided to focus the study on the period 2020-2023. In this sense, the decision is made to carry out an analysis of the post-pandemic results, therefore, the Pearson R correlation coefficient between public spending and tourist arrivals is identified equal to R = 0.545 and the value Sig. bilateral=0.029; resulting significant, reaching the conclusion that an increase in public spending on tourism executed by the Regional Government of Loreto is associated with an increase in the arrival of tourists to the department of Loreto during the period 2020-2023.